Separate Legal Entity of Corporation: The Corporate Veil - Waqas, Muhammad; Rehman, Zahoor (International Journal of Social Sciences and Management, 2016)
The concept of separate legal entity is 500 years old and it means that the corporation is separate in all spheres of its activities. It is separate from its owner, from its employees and due to this separation between the corporation and an individual the shareholders’ liability is also limited. A corporation is established through four different ways i.e. continuity, self-governance, identification persona, and specification of assets. The personhood of a corporation is evolved with the passage of time through different court judgments in which Salomon case plays the role of corner stone. The corporation can own, sell and buy property in its name. The corporation can sue and be sued in the court of law as a legal person. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 1-4